Genome-Wide Association Study of Egg-Laying Traits and Egg Quality in LingKun Chickens - Gao, Jinfeng; Xu, Wenwu; Zeng, Tao; Tian, Yong; Wu, Chunqin; Liu, Suzhen; Zhao, Yan; Zhou, Shuhe; Lin, Xinqin; Cao, Hongguo; Lu, Lizhi (Frontiers in Veterinary Science, 2022)
Egg production is the most important trait of laying hens. To identify molecular markers and candidate genes associated with egg production and quality, including body weight at ﬁrst oviposition (BWF), number of eggs produced in 500 days (EN500), Egg weight (EW), egg shell thickness (EST), egg shell strength (ESS) and Haugh unit (HU), a genome-wide analysis was performed in 266 LingKun Chickens. The results showed that thirty-seven single nucleotide polymorphisms (SNPs) were associated with all traits (P＜9.47*10-8 , Bonferroni correction). These SNPs were located in close proximity to or within the sequence of the thirteen candidate genes, Including GAL, CENPF, GPC2, PEMT, TFAP2D, CPQ gene related to egg-laying and SLC5A7, NCALD, PSMB2, SLIT3 and TTLL7 genes related to egg quality. Interestingly, one of the genes involved in bone formation (SLIT3) was identified as a candidate gene for ESS. Our candidate genes as well as SNPs associated with egg-laying traits were significant for molecular breeding of egg-laying traits and egg quality in LingKun chickens.